Kamus istilah ekonomi, keuangan, dan bisnis syariah A-Z - Sholahuddin, Muhammad (Jakarta : Gramedia Pustaka Utama, 2011)
Indonesian dictionary of Islamic economic terms.
Includes bibliographical references (p. [195]).
Keywords: Economics -- Dictionaries -- Indonesian; Economics -- Religious aspects -- Islam -- Dictionaries -- Indonesian; Islam -- Economic aspects -- Dictionaries -- Indonesian; Arabic language -- Dictionaries -- Indonesian; English language -- Dictionaries -- Indonesian